Non-severe Serovar Type E Capnocytophaga canimorsus Infection in a Post-splenectomy Male: A Case Report - Horiuchi, Hiroshi; Suzuki, Michio; Imaoka, Koichi; Hayakawa, Syo; Niida, Shoko; Okano, Hiromu; Otsuka, Tsuyoshi; Miyazaki, Hiroshi; Furuya, Ryosuke (Curēus (Palo Alto, CA), 2023)
(CP) causes severe infections in immunocompromised individuals. Three serovars (A, B, and C) are known to be responsible for more than 90% of infections associated with dog bites, although these three constitute only 8% of the serovars carried by dogs. We experienced a post-splenectomy non-severe case of CP withserovar type E, which has never been isolated in Japan. The prognosis of type E CP infections may be better than that of types A, B, and C infections because of the disproportion of serovars between clinical human isolates and dog oral isolates.